Civil Law Analysis of the Misuse of Legal Entities for Personal Interests (Piercing the Corporate Veil) in Indonesia - Judijanto, Loso; Triyantoro, Andri; Susilo, Anton (The Easta Journal Law and Human Rights, 2025)
This paper explores the concept of "piercing the corporate veil" within the context of Indonesian corporate law, focusing on the misuse of legal entities for personal interests. In Indonesia, the separation of a corporation's legal identity from its shareholders and directors typically shields them from personal liability. However, in cases of fraud, misconduct, or abuse, the legal doctrine of piercing the corporate veil allows courts to disregard the corporate entity and hold individuals personally accountable. Through a normative juridical analysis, this study examines relevant legal statutes, judicial decisions, and case law to assess the application of this principle in Indonesia. The paper identifies key factors influencing the decision to pierce the corporate veil, such as fraud, misrepresentation, and evasion of obligations. It also compares Indonesia's approach with international practices, highlighting areas for improvement. The findings indicate that while the concept of piercing the corporate veil is applied in Indonesia under exceptional circumstances, its inconsistent application and lack of a comprehensive legal framework pose challenges to corporate governance and accountability. The study concludes with recommendations for legal reform and enhanced enforcement mechanisms to better address corporate abuse and protect public and stakeholder interests.